Bats in the Anthropocene: Conservation of Bats in a Changing World - Voigt, Christian C.; Kingston, Tigga (Springer Nature, 2016)
Conservation Biology/Ecology; Vertebrates; Animal Ecology; Climate Change/Climate Change Impacts